The landscape of chimeric antigen receptor T cell therapy in breast cancer: Perspectives and outlook - Zhang, Hao; Zhu, Shuangli; Deng, Wanjun; Li, Rui; Zhou, Haiting; Xiong, Huihua (Frontiers in Immunology, 2022)
Chimeric antigen receptor-T (CAR-T) cell therapy is a revolutionary adoptive cell therapy, which could modify and redirect T cells to specific tumor cells. Since CAR-T cell therapy was first approved for B cell-derived malignancies in 2017, it has yielded unprecedented progress in hematological tumors and has dramatically reshaped the landscape of cancer therapy in recent years. Currently, cumulative evidence has demonstrated that CAR-T cell therapy could be a viable therapeutic strategy for solid cancers. However, owing to the immunosuppressive tumor microenvironment (TME) and heterogenous tumor antigens, the application of CAR-T cell therapy against solid cancers requires circumventing more challenging obstacles. Breast cancer is characterized by a high degree of invasiveness, malignancy, and poor prognosis. The review highlights the underlying targets of CAR-T cell therapy in breast cancer, summarizes the challenges associated with CAR-T cell therapy, and proposes the strategies to overcome these challenges, which provides a novel approach to breast cancer treatment.